LIFE HEALTHCARE ESIDIMENI: A (HUMAN RIGHTS) DREAM DEFERRED - Leoni van der Merwe (Obiter, 2018)
This article delves into South Africa’s compliance with its obligations in terms of the United Nations Convention on the Rights of Persons with Disabilities in light of the deaths of 144 mental health patients transferred from the Life Healthcare Esidimeni facility to various nongovernmental organisations during 2016. Consideration is given to South Africa’s constitutional framework as well as the overall enforcement mechanisms and application of the said Convention in Africa given the existence of unique challenges such as HIV/AIDS, poverty and a scarcity of resources. The article recognises the importance of transcending beyond policy development, approval and publication to improve the lives of persons with disabilities in South Africa.